2015
DOI: 10.5352/jls.2015.25.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity and Chemical Characteristics of Cordyceps militaris Powder Fermented by Several Microscopic Organisms

Abstract: The comparative effects of the fibrinolytic action, antioxidative activity, and tyrosinase inhibition of Cordyceps militaris powder and fermented Cordyceps militaris powders were investigated using several microscopic organisms. The nutritional components such as phenolic compounds, flavonoids, and minerals were also measured. The total phenolic compounds and flavonoid concentrations were highest in the Cordyceps militaris powder fermented by Aspergillus oryzae. Major minerals were K, Ca, Mg, and Zn. Native po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…At present, the main ingredient of Jin-shui-bao capsule (a drug sold in the Chinese market) is Fermented C. sinensis powder. Fermented C. sinensis powder has similar efficacy to C. sinensis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main ingredient of Jin-shui-bao capsule (a drug sold in the Chinese market) is Fermented C. sinensis powder. Fermented C. sinensis powder has similar efficacy to C. sinensis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used for the treatment of chronic hepatitis and kidney failure (Pan, Zhang, & Ni, 2013). These curative effects of Cordyceps sinensis could be attributed to their active chemical components, including nucleosides (Cheng, Zhang, & Song, 2017), sterols (Sun, Zhao, & Dang, 2016; Yuan, Wang, & Kuang, 2007), polysaccharides (Yan, Wang, & Li, 2011), amino acids (Wei, Xu, & Wu, 2014), flavonoids, and other trace elements (Ahn, Park, & Yoon, 2015; Zhao, Xie, & Wang, 2014). The types and quantities of bioactive components in fermented Cordyceps sinensis vary with the number of strains and fermentation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, modern pharmacological and clinical studies have also revealed that fermented Cordyceps sinensis can have a major impact on the treatment of chronic hepatitis and kidney failure. These curative effects could be attributed to their active chemical components, including nucleosides, polysaccharides, sterols, amino acids, flavonoids, and metal complexes [ 4 – 8 ]. The type and quantity of the bioactive ingredients in fermented Cordyceps sinensis vary with the strain and the condition of the material [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%